Evaluation of primers targeting chromo helicase DNA-binding gene (CHD) for molecular sexing identification in four bird families - Fitriana, Fauziah; Resita, Riza; Disastra, Yuda; Setyorini, Dian Ritma; Haryanto, Aris; Aziz, Fatkhanuddin (Livestock and Animal Research, 2023)
Objective: Sex determination of birds is crucial role in breeding and conservation purposes. Genomic approaches by using basis of bird sex polymorphism are accepted to generate an accurate sexing procedure. The PCR method is commonly used and known to provide accurate test results in determining the sex of birds, but its successes is strongly influenced by the compatibility of the primers used with the DNA template. This study aimed to determine the potential use of CHD1LF/CHD1LR targeting CHD gene fragment in 4 species from Phasianidae, Psittacidae, Estrildidae, and Passeridae families.Method: Blood samples (n= 30) from representatives of species in 4 families above were collected for DNA isolation, then PCR test was performed using CHD1LF/CHD1LR primers. The PCR results obtained were compared with positive controls, necropsy examination and information from bird sellers.Result: The results showed that the primer CHD1LF/CHD1LR could be used in Phasianidae,Psittacidae, Estrildidae, and Passeridae families. The PCR product was confirmed to be same as well as the positive control and necropsy results. It is demonstrated that male birds showed a single band (474 bp), while double bands (474 and 319 bp) were observed in female birds. Different accuracies were observed during this study between molecular approach and manual sexing by bird seller i.e:sparrows (46%) and finches (50%), while the accuracy of parakeets was 75%, and quails 80%.Conclusions: Primer CHD1LF/CHD1LR can be used to determine the sex of birds from the familiesPhasianidae, Psittacidae, Estrildidae, and Passeridae. Our study showed that molecular-based method is valuable and able to reduce error rate to 100% in bird sexing procedures.